Ideologies in English-Indonesian Dissertation Abstracts Translation: An Explanatory Case Study - Farkhan, Muhammad; Sayogie, Frans (Buletin Al-Turas, 2024)
PurposeThe study aimed to reveal how the students applied the ideology of domestication and foreignization in producing Indonesian-English dissertation abstracts on Islamic studies.MethodUsing a qualitative approach with an explanatory case study design, it relied on Indonesian and English abstracts as the primary data sources, taken randomly from the repository of UIN Jakarta. As the main instrument, the researcher compared the English abstracts to Indonesian ones syntactically and lexically to identify the implemented strategies that reflect the translation ideology of domestication and foreignization.Result/FindingThe study revealed that in translating sentences from the SL to the TL, the dominant strategies involving some lexical and grammatical changes were a reader-oriented process; while in translating culture-specific items from the SL to the TL, the dominant strategies were a writer-oriented process with fewer changes or adaptation.ConclusionThe study concludes that the foreignization ideology dominates translating culture specific items, while the domestication ideology hegemonies translating sentences of the dissertation abstracts.